PENGELOLAAN SAMPAH DI PASAR BARU KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Julaini Julaini (Pelantar Press, 2024)
Waste can be defined as a burden or valuable resource depending on how waste is managed. Waste generation in an area is generally determined by the economic level of the community. Where, the economic level of a society is directly proportional to the level of consumption. The high level of the economy means that the waste generated is also increasing. Waste management is needed to anticipate the waste generated in an area such as Pangkalan Kerinci District. The population in Pangkalan Kerinci is 103,465 thousand people (BPS Pelalawan Regency). And produce waste as much as 0.5 kg/capita/day. There was an increase in the amount of waste generation in Pangkalan Kerinci, such as in 2016 the amount of waste generation was 14,070 tons, while the level of solid waste service in Pangkalan Kerinci City only reached 24.8%, while 75.2% of the public had not received solid waste services. Particularly in the Pasar Baru area, waste services are only as large as (field data). The Waste Management Strategy at Pasar Baru, Pangkalan Kerinci is expected to create beauty, cleanliness and public health as well as reduce waste reduction that will go to TPA, calculation of potential sellers and market managers and the Environmental Service Life, is also expected to be a consideration in waste management. As well as the irregular schedule for garbage collection due to the lack of participation from the community to follow the directions and socialization given by the Environmental Service to dispose of garbage before the time of garbage collection so that garbage is transported and there is no buildup which hampers the implementation of waste management.